(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The current research sought to identify the obstacles to implementing blended learning in the open education program at Latakia University, and ways to activate it from the perspective of faculty members. The research sample was selected by a simple random method, and its number was (96) faculty members. To achieve the aims of the research, the researchers adopted the descriptive research methodology and used a questionnaire of faculty members opinions about the obstacles to implementing blended learning in the open education and ways to activate it (prepared). The research showed these results: The obstacles to implementing blended learning in the open education according to the opinions of the faculty members are present to a high degree, and with a materiality weight of (86%). The obstacles related to the faculty members came first, followed by those related to the infrastructure, then those related to the students, and in the last those related to the curriculum. The most important ways to activate the application of blended learning is to provide the necessary infrastructure, train students to use the blended learning system, train faculty members to prepare blended learning courses, and increase educational activities supporting its application.